Brucella abortus inhibits IFN-γ-induced FcγRI expression and FcγRI-restricted phagocytosis via toll-like receptor 2 on human monocytes/macrophages - Barrionuevo, Paula (2011)
The strategies that allow Brucella abortus to persist for years inside macrophages subverting host immune responses are not completely understood. Immunity against this bacterium relies on the capacity of IFN-γ to activate macrophages, endowing them with the ability to destroy intracellular bacteria. We report here that infection with B. abortus down-modulates the expression of the type I receptor for the Fc portion of IgG (FcγRI, CD64) and FcγRI-restricted phagocytosis regulated by IFN-γ in human monocytes/macrophages. Both phenomena were not dependent on bacterial viability, since they were also induced by heat-killed B. abortus (HKBA), suggesting that they were elicited by a structural bacterial component. Accordingly, a prototypical B. abortus lipoprotein (L-Omp19), but not its unlipidated form, inhibited both CD64 expression and FcγRI-restricted phagocytosis regulated by IFN-γ. Moreover, a synthetic lipohexapeptide that mimics the structure of the protein lipid moiety also inhibited CD64 expression, indicating that any Brucella lipoprotein could down-modulate CD64 expression and FcγRI-restricted phagocytosis. Pre-incubation of monocytes/macrophages with anti-TLR2 mAb blocked the inhibition of the CD64 expression mediated by HKBA and L-Omp19. These results, together with our previous observations establish that B. abortus utilizes its lipoproteins to inhibit the monocytes/macrophages activation mediated by IFN-γ and to subvert host immunonological responses. © 2010 Institut Pasteur.